1991
DOI: 10.2307/1591324
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Poxvirus from Debilitating Cutaneous Lesions on Four Immature Grackles (Quiscalus sp.)

Abstract: Poxvirus was isolated from nodules on four immature grackles (Quiscalus sp.) collected in two residential areas of Victoria, Texas. All of the birds were emaciated and had nodules on the eyelids, bill, legs, toes, and areas of the skin on the wings, neck, and ventral abdomen. These pox nodules were extensive and probably interfered with both sight and flight. The preliminary diagnosis was confirmed by virus isolation, histopathology, and electron microscopy. Poxvirus was isolated on the chorioallantoic membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 3 publications
3
25
0
Order By: Relevance
“…This has been documented in similar occurrence of avianpox in other avian species (Mc Donald et al, 1981;Docherty et al, 1991;Ostrowski et al., 1995;Gerlach et al, 1998;Kreuder et al, 1999;Catroxo et al, 2009). …”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This has been documented in similar occurrence of avianpox in other avian species (Mc Donald et al, 1981;Docherty et al, 1991;Ostrowski et al., 1995;Gerlach et al, 1998;Kreuder et al, 1999;Catroxo et al, 2009). …”
Section: Discussionsupporting
confidence: 66%
“…By means of the negative staining technique, poxvirus particles were identified in suspension of skin fragments, as been seen in other cases (Tantawi et al, 1981;Terragino et al, 1981;Docherty et al,1991;Allwright et al, 1994;Gulbahar et al, 2005;Kulich et al, 2008;Catroxo et al, 2009;Shivaprasad et al, 2009). …”
Section: Wwwintechopencomsupporting
confidence: 52%
“…Avian poxvirus Poxvirus avium occurs in at least 60 species of wild birds (Kirmse 1967a), though few studies describe the effects of avian pox on wild bird populations (Kirmse 1969, Kirmse and Loftin 1969, Vargas 1987, Wilson and Crawford 1988, Curry and Grant 1989, Docherty et al 1991, Forrester 1991, Buenestado et al 2004.…”
mentioning
confidence: 99%
“…Both types can be readily diagnosed by observing proliferation of the epithelium, with cells containing large cytoplasmic viral inclusion bodies (Karstad 1971). Cutaneous avian pox is most commonly observed in wild birds and is characterised by the development of nodular wart-like, swollen lesions on bare or unfeathered parts of the head, legs, feet, and sometimes parts of the wings and ventral abdomen (Docherty et al 1991, Tripathy 1993. The diphtheritic form causes high mortality in domestic bird species and results in lesions appearing in the oral cavity, digestive, or upper respiratory tract (Bolte et al 1999), but has not been reported in Darwin's finches or any other wild Galápagos species (J. Bollmer pers.…”
mentioning
confidence: 99%
“…The transmission electron microscopy technique has been a method of choice to diagnose poxvirus in clinical samples of scabs and skin lesions due to rapid and easy preparation to detect these agents (Nitsche et al, 2006) and others agents causing vesicular diseases (Hazelton et al, 2003). Many workers have used transmission electron microscopy for identification of poxvirus infections in animals and birds from clinical samples and was considered to be very effective tool as it allows easy identification of the agents (Catroxo et al, 2009;Docherty et al, 1991;Nitsche et al, 2006). Use of EM for identification of the agent in the present study also revealed similar finding with the previous workers.…”
Section: Molecular Characterization and Phylogenetic Analysismentioning
confidence: 99%